Triad. Method for studying the core of the semiotic parity of language and art - Breskin, Vladimir (Signs - International Journal of Semiotics, 2010)
The purpose of this paper is to present and describe a new method for studying pre-speech language. The suggested approach allows correlate epistemology of linguistics to the ideological tradition of other scientific disciplines. Method is based on three linguistic categories – nouns, verbs, and interjections in their motor and expressive qualities – and their relation to the three basic forms of art – graphics (visual art), movement (dance), and sound (music). The study considers this correlation as caused by the nature of the human receptor system. This method explains the nature of art and the phenomenon of aesthetics and allows for the chronological arrangement of important cultural processes; it identifies the fundamental unanimity of the semiotic nature of language and art.